2020
DOI: 10.3390/s20133616
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Measurement of Skeletal Muscle Contractile Parameters Using Flexible and Wearable Single-Element Ultrasonic Sensor

Abstract: Skeletal muscle is considered as a near-constant volume system, and the contractions of the muscle are related to the changes in tissue thickness. Assessment of the skeletal muscle contractile parameters such as maximum contraction thickness ( T h ), contraction time ( T c ), contraction velocity ( V c ), sustain time ( T s ), and half-relaxation ( T r ) provides valuable information for various medical applications. This paper presents a single-element wearable ultrasonic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 123 publications
0
16
0
Order By: Relevance
“…Adapted from Akhlaghi et al (2016) . Copyright 2016, IEEE; (D) the photo of wearable ultrasonic sensor developed by AlMohimeed and Ono (2020) . Reproduced with permission ( AlMohimeed and Ono, 2020 ).…”
Section: Biomechanical Sensing Interfacesmentioning
confidence: 99%
“…Adapted from Akhlaghi et al (2016) . Copyright 2016, IEEE; (D) the photo of wearable ultrasonic sensor developed by AlMohimeed and Ono (2020) . Reproduced with permission ( AlMohimeed and Ono, 2020 ).…”
Section: Biomechanical Sensing Interfacesmentioning
confidence: 99%
“…Crystalline and ceramics are common piezoelectric materials but the most commonly used piezoceramic is lead zirconate titanate (PZT) [5] due to its high electromechanical coupling coefficient and its very adequate dielectric and elastic properties for biomedical imaging. Other materials of interest inlude polyvinylidene fluoride (PVDF), shown to have great flexibility and biocompatibility [8], and Aluminium Nitride (AIN) which offers higher sensitivity than PZT [9]. These materials were analysed in different studies (Table 1) to evaluate the optimum configuration for SMG applications.…”
Section: A Structure and Principlementioning
confidence: 99%
“…Another work published in 2020 made use of 1-D SMG signals to measure acoustic nonlinearity parameters and showed that they have the potential to represent skeletal muscles dynamically [ 20 ]. An additional publication from 2020 presented a single element wearable ultrasonic sensor, consisting of a transmitter and receiver, and a corresponding method to measure skeletal muscle contractile parameters [ 21 ].…”
Section: Introductionmentioning
confidence: 99%